Granulomatous diseases: Oral manifestations and recommendations - Ahmed A. Alhassani; Mohammad S. Al-Zahrani; Khalid H. Zawawi (Saudi Dental Journal)
Granulomatous diseases may present with oral manifestations that are detectable by dental care providers. In certain cases, oral manifestations may precede systemic signs and symptoms. Dentists managing patients with these conditions may modify the dental treatment plan and possibly retain the support of other health professionals. This review gives an update on granulomatous diseases that can be faced by the dental practitioner.